Gender Occupational Segregation in Haryana: A District Level Analysis Based on National Classification of Occupations - SHARMA, HEMLATA (The journal of contemporary issues in business and government, 2021)
This paper analyses Gender occupational segregation in Haryana using census data for National classification of occupations for 2001 and 2011. The value of Duncan’s index of dissimilarity shows that during 2001 and 2011, segregation has declined in Haryana. Both At aggregate level and at sectoral level. It declined for total, main and marginal workers in rural sector. However, in urban sector Gender occupational segregation declined for total and main workers and increased for marginal workers. Our results show that segregation is higher among main workers in rural sector and marginal workers in Urban sector. Also, segregation is higher in urban sector as compared to rural sector. Our results also show that segregation is higher among districts of Mewat, Mahendergarh and Rewari which are socially backward and is least among developed districts of Panchkula, Panipat, Gurgaon and Karnal.